2018
DOI: 10.1186/s12940-018-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to phthalates and autism spectrum disorder in the MARBLES study

Abstract: BackgroundEvidence from experimental and observational studies suggests that prenatal phthalate exposures may be associated with autism spectrum disorder (ASD). We examined whether prenatal phthalate exposures were associated with an increased risk of ASD.MethodsWe quantified 14 metabolites of eight phthalates in 636 multiple maternal urine samples collected during 2nd and 3rd trimesters of pregnancy from 201 mother-child pairs in MARBLES (Markers of Autism Risk in Babies – Learning Early Signs), a high-risk A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 86 publications
3
46
2
2
Order By: Relevance
“…To our knowledge, this is the first study to report on these potential protective effects of folate supplementation in regard to the relationship between phthalates exposure and autistic traits. Similar effect modification by prenatal vitamin use has been reported for the associations between MCPP and mono-carboxyisooctyl phthalate (MCOP) and nontypical development (Shin et al 2018). In addition, Shin et al (2018) reported protective effects of mono-isobutyl phthalate, MCPP, and MCOP in relation to child's ASD risk in mothers who reported prenatal vitamins use, and null associations in children of mothers who reported no prenatal vitamins use.…”
Section: Srs Subscale Phthalatesupporting
confidence: 61%
See 3 more Smart Citations
“…To our knowledge, this is the first study to report on these potential protective effects of folate supplementation in regard to the relationship between phthalates exposure and autistic traits. Similar effect modification by prenatal vitamin use has been reported for the associations between MCPP and mono-carboxyisooctyl phthalate (MCOP) and nontypical development (Shin et al 2018). In addition, Shin et al (2018) reported protective effects of mono-isobutyl phthalate, MCPP, and MCOP in relation to child's ASD risk in mothers who reported prenatal vitamins use, and null associations in children of mothers who reported no prenatal vitamins use.…”
Section: Srs Subscale Phthalatesupporting
confidence: 61%
“…In contrast, three other studies did not observe associations of phthalates in second and third trimester maternal urine (Braun et al 2014;Shin et al 2018) or house dust collected 2-5 y after birth (Philippat et al 2015) with autistic traits or ASD diagnosis. However, one of those studies reported potential effect modification of the association between some phthalates and ASD by prenatal vitamin use (Shin et al 2018). In addition, two recent studies suggested that folic acid (FA) may mitigate the potential adverse health effects of air pollutants and pesticides in relation to ASD (Goodrich et al 2018;Schmidt et al 2017).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Much more information is needed to understand which patient populations are most responsive, and whether probiotic treatment would be a valuable alternative. Importantly, there have also been many environmental exposures associated with the development of ASD [180][181][182][183], and more research into the role of the microbiome could help elucidate mechanisms. ASD is just one example of a psychiatric outcome that may sit at the crossroads of microbial dysbiosis and environmental exposure.…”
Section: Environmental Exposures and The Microbiome-gut-brain Axismentioning
confidence: 99%